Leveraging Inventory Management for Enhanced Performance in Elementary School Cooperatives: Case Study from Majalengka Regency - Sutarman, Sutarman; Purnomo, Agus; Mety Zalynda, Putri (Elementary Teacher Education Program, Majalengka University, 2024)
Cooperatives play a significant role in promoting economic growth by not only increasing community income but also providing employment opportunities in the small business sector. For cooperatives to effectively support the economic development of villages, it is crucial for them to function as healthy business entities. One way to enhance their efficiency is by ensuring consistency in their managerial activities, ranging from planning to control, including inventory management. SD